Zakaj je Blejsko jezero še vedno evtrofično? - Rismal, Mitja (Gradbeni vestnik, 2019)
The article tries to answer the question, why after 50 years the lake of Bled with a volume of 25,7.106 m3, surface of 1,45 km2, and max. depth of 30,6 m, with surface flashing with clean water from river Radovna since 1970, and with bottom flashing since 1980, still has not improved to oligotrophic state.
Keywords: ecological modeling of lakes; ekološko modeliranje jezer; engineering ecology; inženirska ekologija; limnologija jezer; limnology of lakes; sanitation of lakes; zdravljenje jezer